MISKONSEPSI PESERTA DIDIK PADA MATERI STRUKTUR DAN FUNGSI TUMBUHAN SAAT PEMBELAJARAN DARING - Indriati Rafidah (STKIP Pesisir Selatan, 2022)
The performance of teachers during the process of online teaching and learning activities is considered not optimal. So that students are likely to misunderstand a concept (misconception). Misconceptions can be remediated by knowing the level of misconceptions in learners. The method that can be used in this case is to use a four-tier diagnostic test or a four-tier test. The source of data in the study was 93 students of class VIII of SMP Negeri 3 Tambang. Misconceptions in students online were 65.34% with details of 64.3%, in the plant tissue sub-concept, 64.0% in the plant organ sub-concept, and 61.5%. On the concept of photosynthesis. The factors that influence misconceptions are the existence of preconceptions in students, less meaningful ways of learning students, learning methods by teachers who lecture too much, lack of supportive facilities either from school or personal facilities, low input from the learners themselves and lack of motivation and support from themselves and parents of students